OPTIMALIZATION OF SOCIAL SECURITY ADMINISTRATION (BPJS KETENAGAKERJAAN) TO ACCELARATE THE ACCESSABILITY OF HOUSING FACILITIES FOR LOW-INCOME PEOPLE ACCELERATING HOUSING FOR LOW INCOME PEOPLE (MBR) - Kawidjaya, Endang (DE'RECHTSSTAAT, 2018)
Housing for low-income people has become a problem that until now cannot be solved completely. Various programs have been launched but the number of backlog of housing continues to grow. One of the parties who take in-charge in this problem settlement is the BPJS Ketenagakerjaan program that launches additional programs related to the housing. The results of this study show the role of BPJS Ketenagakerjaan in Accelerating the Accessibility of Housing Facilities for Low-Income People with several programs such as down-payment facilities (PUMP), home renovation loans (PRP) and real estate construction loans. These programs will assist the government to settle this housing deficit although there has not been any prevailing rule and regulation which also has not reached entire nation of Indonesia due to it is limited to the members of BPJS Ketenagakerjaan. Therefore it is required to optimize the role of BPJS Ketenagakaerjaan to settle such housing deficit by understanding the prevailing rules and regulation and some related facilities including the application of leasing. The obstacle which inhibited by the BI Checking that can be solved by set up the new scheme to the potential debtors that so that they can as soon as possible live in their dream houses though still own difficulties in credit rate/BI-Checking. Then, as they change their credit rate they may purchase the house in the form of mortgage based on their capacity of income. To execute this, strong rules and regulation from the government as basis of the role of BPJS Ketenagakerjaan or “other LKNB”can also be active in this housing deficit problem with leasing scheme.